2019
DOI: 10.2147/cmar.s200922
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long noncoding RNA DANCR in various cancers: a meta-analysis and bioinformatics</p>

Abstract: Background Differentiation antagonizing non-protein-coding RNA (DANCR) is a novel long noncoding RNA. Recent studies have shown that DANCR is aberrantly expressed in several types of cancer and is associated with poor outcomes. However, the clinical diagnostic significance of DANCR in tumors is not completely understood. Methods We searched the PubMed, Medline, Web of Science, EMBASE, Cochrane Library, and Ovid databases (up to December 30, 2018) for relevant literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Several lncRNAs have been documented to regulate the growth and metastasis of CC [11,12]. LncRNA differentiation antagonizing non-protein-coding RNA (DANCR) has recently been found to act as an oncogenic driver in several cancer type and correlated with tumor growth and metastasis [13]. Importantly, abnormal up-regulation of DANCR has been revealed to be linked with advanced tumor progression of CC [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several lncRNAs have been documented to regulate the growth and metastasis of CC [11,12]. LncRNA differentiation antagonizing non-protein-coding RNA (DANCR) has recently been found to act as an oncogenic driver in several cancer type and correlated with tumor growth and metastasis [13]. Importantly, abnormal up-regulation of DANCR has been revealed to be linked with advanced tumor progression of CC [14].…”
Section: Introductionmentioning
confidence: 99%
“…The fixed-effect model was applied when I 2 > 50% and P > 0.05. Otherwise, the random-effect model was used [7]. The publication bias was assessed by the Funnel plots and Begg's test, and sensitivity analysis was performed to examine the robustness of results.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that lncRNAs play vital roles in various physiological and pathological process of cancers, including cell proliferation, migration, invasion, and metabolism by functioning as oncogene or tumor suppressor [4][5][6]. Furthermore, growing evidence has demonstrated that lncRNAs can be recognized as tumor-specific prognostic predictors for some cancers, and recent meta-analyses have suggested several lncRNAs correlated with prognosis and chinicopathological features as candidates for precise prognosis prediction of cancers, such as DANCR [7], CRNDE [8] and MVIH [9].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown that lncRNA is abnormally expressed in many human cancers, and it plays an important role in the initiation and progression of cancer. Previous meta-analyses have indicated that ZEB1-AS1 [1], MALAT1 [2], SNHG1 [3], DANCR [4], and HOTAIR [5] are related to the clinicopathological features and prognosis of tumors. These findings demonstrate that lncRNA may be a tumor-specific prognostic biomarker and therapeutic target [6].…”
Section: Introductionmentioning
confidence: 99%